COMPARISON OF 3D PRINTER AND WOOD CASTING PATTERN - Hamid Abdillah; Muhammad Munadi; Nur Wachid Supriyadi (Politeknik Caltex Riau, 2020)
Cast patterns are replicas of objects used as a reference in the casting process. Making cast patterns is still dominated by conventional processes using wood. This study aims to compare the conventional wood cast patterns with cast patterns made using a 3D printer. This research was conducted by making cast pattern products using conventional methods and 3D printers. Conventional pattern making uses a woodworking process while the 3D printer pattern uses a 3D printer stereolithography (SLA) system. Conventional cast patterns and 3D printer products are then compared in terms of geometric quality and size precision. The results obtained are the cast patterns made with a 3D printer have an advantage in precision the size is better than conventional patterns. As for the quality of the geometry and surface roughness both methods have good results. this opens the opportunity to conduct a more in-depth review of 3D printer applications in the metal casting sector